2013
DOI: 10.1038/leu.2013.206
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of IKZF1 and SPRED1 are associated with poor prognosis in a population-based series of pediatric B-cell precursor acute lymphoblastic leukemia diagnosed between 1992 and 2011

Abstract: , Castor, A., Behrendtz, M., Biloglav, A., Forestier, E., Paulsson, K., & Johansson, B. (2014). Deletions of IKZF1 and SPRED1 are associated with poor prognosis in a population-based series of pediatric B-cell precursor acute lymphoblastic leukemia diagnosed between 1992 and 2011. Leukemia, 28(2), 302-310. DOI: 10.1038DOI: 10. /leu.2013 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 48 publications
8
75
2
1
Order By: Relevance
“…CDKN2A and CDKN2B as well as BTLA and CD200 genes were co-deleted in all cases, thus the pairs are merged into one column. Deletion of ATP10A was recently shown to be a recurrent aberration in BCP-ALL, associated with decreased 10-year event-free survival 56 . Gray indicates loss, black indicates a gain, deleted exons within IKZF1, ABL1 and ETV6 genes are indicated by numerals (for IKZF1 white numerals depict losses resulting in a dominant negative IKZF1 isoform or complete loss of IKZF1 expression, black numerals depict haploinsufficiency with the potential exception of combined 2-3/4-7 loss which can affect either a single allele or both gene alleles and thus can result in either haploinsufficiency or complete loss).…”
Section: Clinical Characteristics Treatment and Outcomementioning
confidence: 99%
“…CDKN2A and CDKN2B as well as BTLA and CD200 genes were co-deleted in all cases, thus the pairs are merged into one column. Deletion of ATP10A was recently shown to be a recurrent aberration in BCP-ALL, associated with decreased 10-year event-free survival 56 . Gray indicates loss, black indicates a gain, deleted exons within IKZF1, ABL1 and ETV6 genes are indicated by numerals (for IKZF1 white numerals depict losses resulting in a dominant negative IKZF1 isoform or complete loss of IKZF1 expression, black numerals depict haploinsufficiency with the potential exception of combined 2-3/4-7 loss which can affect either a single allele or both gene alleles and thus can result in either haploinsufficiency or complete loss).…”
Section: Clinical Characteristics Treatment and Outcomementioning
confidence: 99%
“…4,7,8 Whether the pattern of microdeletions, as ascertained by single nucleotide polymorphism (SNP) array analysis, also differs between childhood and adult BCP ALL is less well clarified because most analyses of ALL have been performed on pediatric cases. 9,10 In fact, SNP array findings in adult ALL have so far been reported in only three larger series, [11][12][13] one of which focused solely on IKZF1 deletions. 13 The two other studies 11,12 identified similar gene deletions to those found in pediatric cases, namely losses of CDKN2A, PAX5, IKZF1, ETV6, RB1, EBF1 and LEF1.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the role of these genes in the development of relapse was described by Mullighan et al (7) in a study showing that deletions in TBL1XR1, BTG1, and NR3C1 are selected for during the clonal evolution of ALL that results in relapsed disease. TBL1XR1 deletions are poor prognostic markers (9) and are enriched during the evolution of relapsed disease (7), indicating a role in GC resistance and eventual relapse.…”
Section: Discussionmentioning
confidence: 99%
“…TBL1XR1 deletions are enriched at relapse compared with diagnosis (6 -8), and importantly TBL1XR1 deletions at diagnosis occur more frequently in patients that ultimately relapse (9). TBL1XR1 is a member of the nuclear receptor corepressor (NCoR) complex and is responsible for the degradation of NCoR (10,11).…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%